EFEKTIVITAS KEMAMPUAN REPSESENTASI MATEMATIS SISWA MENGGUNAKAN PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) DI SMA NEGERI 1 ANGKOLA TIMUR - Helmi Saleha Siregar; Muhammad Syahril Harahap (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2019)
abstract This study aims to describe the effectiveness of using RME approach on students’ mathematical representation ability at the tenth grade students of SMA Negeri 1 Angkola Timur. The research was conducted by using experimental (pretest post test one group design) method with 26 students as the sample and they were taken by using cluster random sampling technique from 78 students. Test and observation were used in collecting the data. Based on descriptive analysis, it could be found (a) the average of using RME approach was 3.5 (very good category) and b) the average of students’ mathematical representation ability before using RME approach was 56.73 (fair category) and after using RME approach was 68.16 (enough category). Furthermore by using inferential statistic (Pair Sample ttest), it could be found significant value was less than 0.05 (0.000<0.05). It means, there is a significant difference of students’ mathematical representation abilitybefore and after using RME approach. The other words, RME approach was effective to increase students’ mathematical representation ability. Keywords: RME approach, mathematical representation ability